PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL PNEUMATIK BERBASIS SOFTWARE SIGIL UNTUK SISWA SMK: PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL PNEUMATIK BERBASIS SOFTWARE SIGIL UNTUK SISWA SMK - Andre Gilang, Andre Gilang Prabowo; Handoyono, Nurcholish Arifin; Widodo, Widodo (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to, (1) Develop e-modules on pneumatics subjects for class X at SMK Muhammadiyah Gamping Sleman, (2) Determine the feasibility of e-modules on pneumatics subjects for class X Light Vehicle Engineering students at SMK Muhammadiyah Gamping. This type of research is a research and development (R&D) project using the 4 D (four-D) development model. The media developed is in the form of learning e-modules. The subjects of this study were class X Light Vehicle Engineering students at SMK Muhammadiyah Gamping Sleman. The object of this research is the learning e-module. The research instrument is a questionnaire. The data analysis technique used in this study is quantitative. The conclusion of this study includes, (1) This study produces an e-learning module containing material arranged in an organized structure, facilitating navigation and understanding (2) The e-module is very feasible to use by reviewing the results of material experts with a score of 83.9%, the results of media experts with a score of 91%. (3) Student responses show a category that is very feasible to use by getting a score of 83%. The conclusion of this study is that the e-module produced is an effective and interactive learning media that allows students to understand the concept of pneumatics more easily and students can access it anytime and anywhere, the feasibility of the e-module learning media in the pneumatics subject is said to be (very feasible) reviewed from the results of the assessment of media experts, material experts and student respondents.